Study of Co-Fe nanocomposite magnetic properties - A.Yu. Salomatina; A.Yu. Fedotov; O.Yu. Severyukhina; F.A. Vinogradov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов)
In this paper, a comparative analysis of the characteristics, advantages and disadvantages of five different types of magnetoresistive random access memories has been carried out. An optimal mathematical model for investigation of composition and structure of materials for spintronics devices is selected. A review of the combined mathematical model consisting of the molecular dynamics method and the model of spin dynamics of particles with interatomic interaction potential based on a modified embedded atom method is presented. An analysis is performed of modeling of magnetic properties of cobalt and iron bilayer film under conditions of the uniform external magnetic field. The iron layer was characterized by the formation of skirmions, while regions with different magnetic domains were found in the cobalt nanofilms. The overall magnetization of the Co-Fe system was found to be low due to the lack of the priority direction of the magnetic moment. The magnetization rates of cobalt, iron of different thicknesses and the Co-Fe system as a whole were compared separately.